2013
DOI: 10.1038/ncomms3286
|View full text |Cite
|
Sign up to set email alerts
|

Tuning organic magnetoresistance in polymer-fullerene blends by controlling spin reaction pathways

Abstract: Harnessing the spin degree of freedom in semiconductors is generally a challenging, yet rewarding task. In recent years, the large effect of a small magnetic field on the current in organic semiconductors has puzzled the young field of organic spintronics. Although the microscopic interaction mechanisms between spin-carrying particles in organic materials are well understood nowadays, there is no consensus as to which pairs of spin-carrying particles are actually influencing the current in such a drastic manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 46 publications
3
149
0
4
Order By: Relevance
“…11 A similar theoretical framework has been applied to account for other microscopic mechanisms and their effect on the magnetic-field dependent current, i.e., magnetoconductance (MC). 12 In recent work 13 we have shown that the dominant mechanism for OMAR in a real device depends on the operating conditions and morphology. Inspired by pioneering work from Wang et al, 8 we blended a polymer and a fullerene and showed that the MC and the underlying spin-based reactions could be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…11 A similar theoretical framework has been applied to account for other microscopic mechanisms and their effect on the magnetic-field dependent current, i.e., magnetoconductance (MC). 12 In recent work 13 we have shown that the dominant mechanism for OMAR in a real device depends on the operating conditions and morphology. Inspired by pioneering work from Wang et al, 8 we blended a polymer and a fullerene and showed that the MC and the underlying spin-based reactions could be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was shown that the magnetic field effect on the current in pristine organic semiconductors is predominantly governed by the reactions between triplet excitons and polarons. 18,20,22,23,25 Moreover, Cox et al recently proposed an analytical model where these reactions are described by the spin-selective formation of socalled metastable trions from triplet exciton-polaron pairs. 23 Their model provides an intuitive explanation of the MC(V) dependence.…”
Section: B Magnetic Field Effectsmentioning
confidence: 99%
“…Accurately measuring and understanding the exact lineshapes of the LFE and HFE is therefore of major importance since the lineshapes can be correlated to the dominant underlying mechanism. 20 In this chapter, we present a detailed study on the voltage and temperature dependence of OMAR, aiming to unravel the magnetic field effects on the current in pristine conjugated polymer devices. Even though OMAR has been studied extensively, there are only a few detailed reports on its temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that a general explanation of the MR effect cannot be given based on a single mechanism. Rather, the dominating mechanism depends not only on the materials and device parameters, but also on operation conditions [35,36]. (a) Possible quasi-particle pairs in organic semiconductors versus energy.…”
Section: Magnetic Field Effects In Organic Semiconductorsmentioning
confidence: 99%